Reflecting on Plastic Surgery Training During Early COVID-19 Pandemic: Resident Exposure and Telemedicine. Issue 6 (28th September 2022) - Epstein, Anabel; Jabori, Sinan Kallo; Wo, Luccie M.; Huberman, Melissa; Samaha, Georges; Ovadia, Steven; Thaller, Seth R.
Abstract : Purpose: Coronavirus disease 2019 (COVID-19) pandemic has been an unprecedented public health crisis. As hospitals took measures to increase their capacity to manage COVID-19 patients, plastic surgeons have also had to modify their routine to continue serving their vital role within the hospital environment. In an effort to reduce exposure to COVID-19 and conserve hospital resources, many plastic surgery programs drastically modified call schedules, restructured inpatient teams, triaged operative cases, and expanded telemedicine encounters. Plastic surgery programs focused on craniofacial procedures were impacted by precautionary preventative protocol and shifts in case load made to protect both the healthcare teams and the patients. At academic centers, plastic surgery trainees of all domains felt the impact of these changes. Recognizing the implications on future craniofacial surgical practice, the pandemic has made, the goal of the authors' study is to measure initial impacts of COVID-19 on plastic surgery trainees using a nationwide survey. The authors' results present the first quantitative analysis of plastic surgery trainees' exposure to COVID-19, deployment to other medical specialties, usage of personal protective equipment, and implementation of telemedicine during the pandemic. While healthcare systems have greatly adapted to pandemic complications and can anticipate vaccination, resurgence of COVID-19 cases linked to the delta variant heightens the authors' urgency in understanding the early pandemic, and its lasting impacts on healthcare. In the months following pandemic onset, telemedicine has become a mainstay in healthcare, trainees have adapted and become integrated in patient care in novel ways, and visits unable to transition to telemedical settings received substantial attention to ensure patient and provider safety. Methods: An institutional review board-approved anonymous, multiple-choice and short-answer, Qualtrics survey regarding plastic surgery resident experiences with COVID-19 exposure. It was sent to all US plastic surgery program directors and program coordinators on April 23, 2020 with the request to distribute the survey to their residents. Residents were given the option to participate in a raffle for a $50 gift card. Outcomes measured included demographics, exposure to COVID-19, availability of resources, and adjustments to residency training practices. Results: Sixty-nine plastic surgery residents throughout all years of training from 18 states responded. Gender, year of training, and location did not significantly impact these reports. Sixteen percent of residents reported covering a COVID-19 team. Twelve percent reported covering a shift not within their scope of practice. From these reports, residents mostly worked in the intensive care unit (50%) and the emergency department (29%). Half of the residents believe they were exposed to high-risk patients. This was reported in a variety of settings: the emergency department for plastic surgery consults (34%), caring for plastic surgery inpatients (16%), performing trauma reconstruction surgery (16%), cancer reconstruction surgery (12%), elective surgery (6%), and intraoperative consults (6%). Seventy-two percent of residents reported adequate access to personal protective equipment. Equipment type varied by patient exposure. When attending to a non-COVID-19 inpatient, most residents used a standard mask (62%) rather than an N95 mask (21%). N95 masks were generally used in patients with unknown COVID-19 status. Residents reported using eye and face shields when attending to non-COVID-19 ICU patients (17%), patients with unknown COVID-19 status (27%), and in the operating room (34%). Forty percent of residents implemented telemedicine to see patients for new consults, follow-up visits, postop checks, and wound checks. Eighty-five percent of residents report that they would continue to incorporate telemedicine in the future. Most significant reported barrier to using telemedicine is the limited ability to perform a physical examination (33%) followed by limited patient access to telemedicine (21%). Other challenges included poor ease of use for patients or providers, billing questions, and lack of interpersonal connection with patients. Conclusion: This study, to the best of the authors' knowledge, is the first to quantitatively investigate how plastic surgery residents have been affected by the widespread impacts of the COVID-19 pandemic. It reports resident exposure to COVID-19 and their associated concerns, resident access to and perceived adequacy of personal protective equipment, as well as changes to clinical practice.